PENINGKATAN KEMAMPUAN MEMAHAMI TATA CARA IBADAH HAJI MENGGUNAKAN METODE NUMBERED HEAD TOGETHER KELAS V MINU WARU I SIDOARJO - Oktavianis, Nur Richa (Journal Of Islamic Elementary School (JIES), 2017)
In learning Fiqh, the research team found difficulties in students' understanding of the material for Hajj procedures. The problem that will be studied in this research is the students' understanding ability. This is important to improve because students are able to understand the material on an average, not only students who are active in class. So the researchers took one method to improve students' understanding, namely the Numbered Head Together Method. The formulation of the problem that will be solved in this problem is increasing the ability to understand the procedures for Hajj by using the Numbered Head Together method and the application of the method in an effort to improve understanding skills. While the purpose of this study is to determine the increase in the ability to understand the procedures for Hajj by using the Numbered Head Togother method and the application of the method in an effort to improve the ability to understand. This study uses classroom action research with Kurt Lewin's model which consists of four stages, namely: planning, implementation, observation, and reflection. This PTK was only carried out in two cycles. The indicator of success in this study is if the student's mastery of the material reaches 80% of the objectives that should be achieved, namely with a KKM score of 80. The results show that the application of the NHT (Numbered Head Together) method in Fiqh learning material on the procedures for the Hajj pilgrimage for class V MINU students Waru I Sidoarjo has been implemented and has increased in each cycle. The increase in the average class from pre-cycle 49 to 71 in the first cycle and to the second cycle is 86 levels, the completeness of the pre-cycle is 3 students or 12% of students who complete, the first cycle is 14 students or 56% of students who complete, Cycle II increased to 96% of students who completed, namely 24 students. The conclusion of this study is that the Numbered Head Together method can have a positive effect.